Percutaneous atrial septal defect closure in Ebstein's anomaly. Issue 2 (4th March 2023) - Cubberley, Alexander T.; Christensen, Jared; Pilgrim, Scott; Gohar, Salman; Wang, Zuyue; Al-Azizi, Karim
Abstract: We report a patient with Ebstein's anomaly, on chronic milrinone therapy for right ventricular failure, who underwent palliative percutaneous closure of her atrial septal defect (ASD) due to recurring strokes. Repeated evaluation of right-sided pressures was performed prior to ASD closure to determine if our patient could tolerate the intervention. Definitive ASD closure was performed under fluoroscopic and transesophageal echocardiogram guidance.